Visualized Experimental Investigation on the Gas-Water Distribution Characteristics in Intersecting Fractures. (26th March 2018) - Wang, Chen; Jiang, Yujing; Liu, Richeng; Wang, Changsheng
Abstract : In coal-bed methane recovery, water is generally drained out along with gas. In order to address the influence of different gas-water ratios, fracture intersecting angles, and gas desorption positions on gas and water distributions along fractures and hence understand the two-phase flow behavior in fracture network, an experimental study was conducted on three artificial models with intersecting fractures. The results show that (1) with gas and water injected at different rates, the flow of water and gas is divided into three stages. In the first stage, gas flowed as small bubbles. The transport of gas was stable, which was similar to single-phase laminar flow. The difference in gas injection positions led to totally contrary flow results of water and gas. (2) In the second stage, larger gas bubbles were formed and the interactions between water and gas became serious. The gas-water distribution was dominated by different inertias between water and gas. The difference in gas injection positions did not take much effect on the gas-water distribution. (3) In the third stage, the influence of the inertia difference was still important, but some other factors also influenced the gas-water distribution. The difference in gas injection positions led to different distribution results. (4) The water injection rate has impact on the distribution of the water flow rate in each outlet. In the second stage, when water was injected at small rates, the difference between the cases in which gas was injected from different positions can be neglected. When water injection rates became larger, this difference became obvious. (5) The intersecting angle of the fractures influences the distribution of water and gas. The larger the intersecting angle is, the larger the inertial effect will be. Consequently, the intersecting angle influences the length of the second stage, which is dominated by the inertial effect.